Rhizosphere soil nutrients and bacterial community diversity of four broad-leaved trees planted under Chinese fir stands with different stocking density levels - Wang, Liyan; Sun, Yangyang; Li, Jing; Tigabu, Mulualem; Xu, Qingli; Ma, Xiangqing; Li, Ming (Frontiers in Forests and Global Change, 2023)
【Objective】Rhizosphere soil nutrients and bacterial diversity of four broad-leaved tree species underplanted in Chinese fir plantation with different stand density levels were analyzed to reveal characteristics of the rhizosphere soil environment and selection of suitable underplanted tree species.【Methods】Chinese fir plantation with three density levels (900, 1200 and 1875 stems ha-1, respectively) were selected and underplanted with Michelia macclurei, Schima superba, Phoebe zhennan and Tsoongiodendron odorum. The rhizosphere soil nutrients and bacterial community of the broad-leaved tree species were determined after four years. 【Results】Significant differences in rhizosphere nutrient content were detected among different tree density levels, where the contents of total K, available K and available P in 900 stems ha-1 stands were significantly higher than the other stocking density levels. There were also significant differences in the contents of total C, total N, total K, available K and available P in the rhizosphere soils of the four trees species, while there were no significant differences in pH and total P. Rhizosphere soil nutrient contents were higher under S. superba and M. macclurei than under P. zhennan and T. odorum. The rhizosphere soil nutrient contents and bacterial diversity decreased with the increase of stand density, and the bacterial diversity showed significant differences in the rhizosphere soils of P. zhennan, T. odorum and S. superba when underplanted in different stand densities. The bacterial diversity was positively correlated with the available P content of rhizosphere soils, suggesting that soil available P content plays an important role in shaping the structure of bacterial community. 【Conclusion】The nutrient contents and bacterial diversity of rhizosphere soils of underplated broad-leaved species decreased with increasing stand density of Chinese fir plantation. Rhizosphere soils of M. macclurei and S. superba were rich in nutrient contents and bacterial diversity. Thus, low density of Chinese fir plantation (900 stems ha-1) underplanted with M. macclurei and S. superba is suitable for the establishment of mixed forest, which will facilitate better tree growth and maintaining soil fertility to realize sustainable management of forests.